DATA-DRIVEN HR ANALYTICS DEPLOYMENT USING DATA SCIENCE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
HR Analytics is a way to amass and evaluate HR data and change the efficiency of an enterprise. Throughdeveloping insight and engagement, HR analytics will maybe add incredible benefit to HR decision-making for workers andorganizations. In this post, we come up with an end-to-end approach to HR analytics that leads to quality data for thedecisions of management. We concentrate on five inclusive issues in the HR department as part of this approach;accordingly, we present strategies that can restrict these challenges. As noted, the aggregation of several fields creates trulyincipient intuitions: we then plan the data collection that could be a coalescence of data from HR, survey data, andmanagement. In addition, we interpret the findings in such a manner that HR can make decisions based on facts and not onconvictions; First by running the Resume Parser, we conduct Text Analytics, which definitely screens the resumes andpotentially spares the manual efforts during recruitment; Second, we cluster the data in a Word cloud that helps to recognizetalent. Additionally, to get more insight into the data, we convert the data. We translate the date of birth to age as part o ftransformations and wages to other preferred currency values. Next on the data collected from the employee survey, weconduct Nostalgic Analytics and later determine the main success metrics. In the end, on an interactive dashboard, wevisualize the information so that HR makes the right decision based on obvious data.